Perancangan Desain Kemasan dan Media Promosi Tango Walut Festive untuk Kebutuhan Perayaan Lebaran di Pasar Modern (International Forum of Researchers and Lecturers, 2024)
This research aims to design packaging and promotional media for the Lebaran edition of Tango Walut products with a focus on increasing consumer appeal in the competitive modern market. The design process includes in-depth analysis of products and markets,exploration of creative ideas, development of attractive designs, and implementation of effective marketing strategies. The resulting packaging design displays typical Eid visual elements with bright colors and illustrations that evoke the spirit of celebration. The marketing strategy implemented involves offline marketing and online marketing with social media campaigns, both of which are designed to increase consumer awareness, interest, desires and purchasing actions. The final result of this design is expected to increase the visibility and sales of Tango Walut products during the Eid period, as well as strengthen the brand's position in the FMCG market.